Six steps towards operationalising freshwater ecoacoustic monitoring. (11th December 2019) - Linke, Simon; Gifford, Toby; Desjonquères, Camille
Abstract: Applications in bioacoustics and its sister discipline ecoacoustics have increased exponentially over the last decade. However, despite knowledge about aquatic bioacoustics dating back to the times of Aristotle and a vast amount of background literature to draw upon, freshwater applications of ecoacoustics have been lagging to date. In this special issue, we present nine studies that deal with underwater acoustics, plus three acoustic studies on water‐dependent birds and frogs. Topics include automatic detection of freshwater organisms by their calls, quantifying habitat change by analysing entire soundscapes, and detecting change in behaviour when organisms are exposed to noise. We identify six major challenges and review progress through this special issue. Challenges include characterisation of sounds, accessibility of archived sounds as well as improving automated analysis methods. Study design considerations include characterisation analysis challenges of spatial and temporal variation. The final key challenge is the so far largely understudied link between ecological condition and underwater sound. We hope that this special issue will raise awareness about underwater soundscapes as a survey tool. With a diverse array of field and analysis tools, this issue can act as a manual for future monitoring applications that will hopefully foster further advances in the field.